1996
DOI: 10.1021/ma951071z
|View full text |Cite
|
Sign up to set email alerts
|

Conformation of Polymer Brushes under Shear: Chain Tilting and Stretching

Abstract: We have studied the conformation of a polymer brush in equilibrium with a solvent that is subject to a shear flow. The interplay between the polymer brush and the hydrodynamic flow of the solvent has been modeled, with simple but largely justifiable approximations. The main technique used in our study is a Monte-Carlo simulation algorithm that is distinct from many standard numerical methods used in studies of polymer brushes in that it combines an off-lattice description of polymer brushesthe Edwards Hamilto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
110
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 25 publications
7
110
0
Order By: Relevance
“…Scaling Relations and Distribution Functions subsection) do not depend on the numerical value of w 2 . In accordance with the choice made in our previous studies, [17][18][19][20] we use the value w 2 ϭ 0.5 in our simulations.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling Relations and Distribution Functions subsection) do not depend on the numerical value of w 2 . In accordance with the choice made in our previous studies, [17][18][19][20] we use the value w 2 ϭ 0.5 in our simulations.…”
Section: Model and Simulation Methodsmentioning
confidence: 99%
“…Estimates for the scaling exponents of the Domb-Joyce model are known from a field-theoretic analysis of high-precision MC data. 15,16 Recently we used discretized Edwards chains in conjunction with off-lattice Monte Carlo simulation schemes for a variety of polymer systems including grafted polymer brushes in a good solvent 17 as well as in a poor solvent, 18 binary brushes in both good and poor solvent, 19 polymer brushes in a good solvent under shear, 20 and diblock copolymer melts. 21,22 The characteristic feature of the models used in these studies is that the volume interaction is formulated as a "virial expansion" in terms of coarse-grained number densities of the effective chain monomers ("vertices").…”
Section: Introductionmentioning
confidence: 99%
“…We have confirmed that 〈f1(x1)〉 ) 〈u1(x2)F(x2)〉 and 〈f2-(x1)〉 ) 0 elsewhere. 46 Other authors have invoked the Brinkman equation in theoretical approaches 15,18,20,26 and MonteCarlo simulations 31,33 of brushes, and also in studying single tethered chains via Brownian dynamics. 23 …”
Section: Calculating the Solvent Velocity In The Brushmentioning
confidence: 99%
“…Several simulation techniques have been used, such as Brownian dynamics, [22][23][24] stochastic dynamics, 25 and dynamic Monte Carlo. [26][27][28] One would expect the most exact results from molecular dynamics simulations, and such simulations have indeed been carried out for symmetric systems consisting of two layers of short grafted polymer chains which are sheared against each other. 29,30 However, most simulations of flow past polymer brushes tend to leave out the solvent molecules and model the solvent as a continuum to save CPU time.…”
Section: Introductionmentioning
confidence: 99%